Adherence to dietary recommendations by socioeconomic status in the United Kingdom biobank cohort study - Carrasco-Marín, Fernanda; Parra-Soto, Solange; Bonpoor, Jirapitcha; Phillips, Nathan; Talebi, Atefeh; Petermann-Rocha, Fanny; Pell, Jill; Ho, Frederick; Martínez-Maturana, Nicolás; Celis-Morales, Carlos; Molina-Luque, Rafael; Molina-Recio, Guillermo (Frontiers in Nutrition, 2024)
Understanding how socioeconomic markers interact could inform future policies aimed at increasing adherence to a healthy diet. This cross-sectional study included 437,860 participants from the UK Biobank. Dietary intake was self-reported. Were used as measures socioeconomic education level, income and Townsend deprivation index. A healthy diet score was defined using current dietary recommendations for nine food items and one point was assigned for meeting the recommendation for each. Good adherence to a healthy diet was defined as the top 75th percentile, while poor adherence was defined as the lowest 25th percentile. Poisson regression was used to investigate adherence to dietary recommendations. There were significant trends whereby diet scores tended to be less healthy as deprivation markers increased. The diet score trends were greater for education compared to area deprivation and income. Compared to participants with the highest level of education, those with the lowest education were found to be 48% less likely to adhere to a healthy diet (95% Confidence Interval [CI]: 0.60-0.64). Additionally, participants with the lowest income level were 33% less likely to maintain a healthy diet (95% CI: 0.73-0.81), and those in the most deprived areas were 13% less likely (95% CI: 0.84-0.91). Among the three measured proxies of socioeconomic statuseducation, income, and area deprivationlow education emerged as the strongest factor associated with lower adherence to a healthy diet.